PENGENALAN DAN IMPLEMENTASI APLIKASI POSPAY KIOS BAGI AGEN SEBAGAI UPAYA PENGEMBANGAN USAHA DI BIDANG LAYANAN PEMBAYARAN DIGITAL - Anggraeni, Kurnia Dwi; Kustini, Kustini (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The advancement of information technology has significantly transformed financial services, including the emergence of digital applications as practical and efficient transaction solutions. One such innovation developed by PT Pos Indonesia is PosPay Kios, a digital platform that enables micro-business actors and the general public to access and offer digital payment services, such as bill payments, money transfers, and e-wallet top-ups. This activity aims to introduce and implement the PosPay Kios application as an effort to develop community-based businesses in the financial services sector. The method used involved direct socialization to the community and MSME players, along with an evaluation of their understanding and response to the application’s use. The results show that the outreach successfully increased digital financial literacy, expanded access to financial services, and created new business opportunities through PosPay Kios partnerships. This program contributes to the realization of financial inclusion and sustainable local economic empowerment